68Ga-FAPI PET/CT for non-invasive characterization and activity assessment of ulcerative colitis and Crohn´s disease - Debus, Josefin; von Götze, Isabelle; Brandt, Johannes; Ehehalt, Robert; Spektor, Anna-Maria; Mildenberger, Philipp; Gauss, Annika; Lang, Matthias; Glatting, Frederik M.; Schreckenberger, Mathias; Kalla, Rahul; Haberkorn, Uwe; et al. (European journal of nuclear medicine and molecular imaging, 2026)
Inflammatory Bowel Diseases (IBD) comprise ulcerative colitis (UC) and Crohn’s disease (CD). Management of IBD requires assessment of disease activity, severity, extent and complications. Here, we describe the signal behavior of both CD and UC in 68Gallium- fibroblast activation protein inhibitor-based radiopharmaceuticals-46-positron emission tomography (68Ga-FAPI-46-PET) and evaluate the potential of 68Ga-FAPI-46-PET for activity assessment in IBD.